2013
DOI: 10.5114/fn.2013.37712
|View full text |Cite
|
Sign up to set email alerts
|

Original article The coexistence of pleomorphic xanthoastrocytoma and arteriovenous malformation. A 

Abstract: A b s t r a c t

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In the literature, AVM has been reported mostly in association with oligodendrogliomas and astrocytomas. 12,17,19 Pleomorphic xanthoastrocytoma 16 , meningioma 9 and ganglioneuroma 5 have also been reported with AVM. Mori et al 14 were the first to report AVM and CP in patients, which were detected radiologically.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, AVM has been reported mostly in association with oligodendrogliomas and astrocytomas. 12,17,19 Pleomorphic xanthoastrocytoma 16 , meningioma 9 and ganglioneuroma 5 have also been reported with AVM. Mori et al 14 were the first to report AVM and CP in patients, which were detected radiologically.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, the primary brain tumours may be accompanied by vascular malformations [27] and such rare coincidence involves mostly gliomas and meningiomas [10,11]. The pathogenetic suggestions consider such angiogliomatic lesions as a result of reactive astroglial neoplastic proliferation second ary to the preexisting vascular malformation.…”
Section: Discussionmentioning
confidence: 99%
“…The particular reason of ALS although it is not completely understood, either genetic plus environmental variables are considered to have a part in its development. Research on the gut microbiome and ALS is still relatively limited, but some studies have reported alterations within a gut microbial community among individuals with ALS as comparison to healthy controls (Naganska and Matyja 2011). Dysbiosis, reduced microbial diversity, and changes in specific bacterial taxa had been associated with ALS.…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 99%